Islet distribution of Peptide YY and its regulatory role in primary mouse islets and immortalised rodent and human beta-cell function and survival. (15th November 2016) - Khan, Dawood; Vasu, Srividya; Moffett, R. Charlotte; Irwin, Nigel; Flatt, Peter R.
Abstract: Recent evidence suggests that the classic gut peptide, Peptide YY (PYY), could play a fundamental role in endocrine pancreatic function. In the present study expression of PYY and its NPY receptors on mouse islets and immortalised rodent and human beta-cells was examined together with the effects of both major circulating forms of PYY, namely PYY(1-36) and PYY(3-36), on beta-cell function, murine islet adaptions to insulin deficiency/resistance, as well as direct effects on cultured beta-cell proliferation and apoptosis. In vivo administration of PYY(3-36), but not PYY(1-36), markedly ( p  < 0.05) decreased food intake in overnight fasted mice. Neither form of PYY affected glucose disposal or insulin secretion following an i.p. glucose challenge. However, in vitro, PYY(1-36) and PYY(3-36) inhibited ( p  < 0.05 to p  < 0.001) glucose, alanine and GLP-1 stimulated insulin secretion from immortalised rodent and human beta-cells, as well as isolated mouse islets, by impeding alterations in membrane potential, [Ca 2+ ]i and elevations of cAMP. Mice treated with multiple low dose streptozotocin presented with severe ( p  < 0.01) loss of beta-cell mass accompanied by notable increases ( p  < 0.001) in alpha and PP cell numbers. In contrast, hydrocortisone-induced insulin resistance increased islet number ( p  < 0.01) and beta-cell mass ( p  < 0.001). PYY expression was consistently observed in alpha-, PP- and delta-, but not beta-cells. Streptozotocin decreased islet PYY co-localisation with PP ( p  < 0.05) and somatostatin ( p  < 0.001), whilst hydrocortisone increased PYY co-localisation with glucagon ( p  < 0.05) in mice. More detailed in vitro investigations revealed that both forms of PYY augmented ( p  < 0.05 to p  < 0.01) immortalised human and rodent beta-cell proliferation and protected against streptozotocin-induced cytotoxicity, to a similar or superior extent as the well characterised beta-cell proliferative and anti-apoptotic agent GLP-1. Taken together, these data highlight the significance and potential offered by modulation of pancreatic islet NPY receptor signalling pathways for preservation of beta-cell mass in diabetes. Highlights: Some evidence infers that Peptide YY (PYY) has a role in pancreatic islet function. PYY inhibited insulin secretion from cultured beta-cells and isolated islets. Insulin deficiency and insulin resistance altered PYY expression. PYY augmented beta-cell proliferation and reduced apoptosis. Modulation PYY islet signalling has potential for preservation of beta-cell mass.